Fatores determinantes para a interrupção do aleitamento materno exclusivo em crianças menores de 1 mês de vida, em Feira de Santana, Bahia - Martins, Camilla da Cruz (2009)
Exclusive breastfeeding (EBF) is considered a suitable practice for healthy growth and development of children. The early interruption of EBF is a problem of global dimension, since it directly affects the health of both mother and son. The aim of this study was to identify the frequency of EBF and assess the determinants for its interruption in the first month of life of children in the city of Feira de Santana, Bahia, Brazil. This is a cohort with 1,309 mother-infant pairs in the city of Feira de Santana. The study started in 2004 and was followed up until 2008. The analysis was divided into two parts: descriptive and analytical, composed of inferential analysis using statistical tests, calculation of measures of association and logistic regression. The statistical program was the SPSS 9.0 and the R. In this study, we identified the prevalence 59.3% of EBF in the first month of life. The lack of previous experience of breastfeeding (PRadjusted=1.24; [IC]95%=1.75-1.43), the presence of nipple fissure (PRadjusted=1.25; [IC]95%=1.09–1.43), use of fixed schedules to suckle (PRadjusted=1.42; [IC]95%=1.09-1.84), the use of pacifiers (PRadjusted=1.53; [IC]95%=1.34-1.76), primiparity (PRadjusted=1.46; [IC9]5%=1.26–1.70), nervousness (PRadjusted=1.40; [IC]95%=1.22–1.62), lack guidance of breastfeeding in the hospital (PRadjusted=1.56; [IC]95%=1.35–1.80), lower education level, or equal to the elementary school (PRadjusted=1.33; [IC]95%=1.14–1.55), lower income (PRadjusted=1.24 [IC]95%=1.06–1.45) and not appreciation of the AM for the father of the child (PRadjusted=1.53; [IC]95%=1.19–1.95) were identified as determinants for early discontinuation of this practice. The present data indicates care practices that improve exclusive breastfeeding rates in the first month of life of the child.